Explaining Sex Differentials in Child Mortality in India: Trends and Determinants. (6th November 2014) - Kuntla, Shrikant; Goli, Srinivas; Jain, Kshipra
Abstract : This study has twofold objectives: (1) to investigate the progress in sex differentials in child mortality in India in terms of within and between group changes and (2) to identify the factors explaining the sex differentials in child mortality and quantify their relative contributions. We have used three rounds of the National Family Health Survey (NFHS) data, 1992 to 2006. Life table approach and Pyatt and Oaxaca decomposition models were used as methods of analyses. The results revealed that though sex differential in child mortality is still high in India, it declined during 1992 to 2006 (Gini index from 0.36 to 0.24). This decline was primarily led by a change in within inequality of female child mortality (Gini index from 0.18 to 0.14). Among the selected predictors, breastfeeding (40%), birth order (24%), antenatal care (9%), and mother's age (7%) emerged as critical contributors for the excess female child mortality in India. From the findings of this study, we suggest that any efforts to do away with gender differences in child survival should focus more on within female child disparity across different population subgroups alongside male-female disparity. Implications are advanced.